Review on Conventional Air Conditioning, Alternative Refrigerants, and CO2 Heat Pumps for Vehicles. (12th November 2013) - Lee, Moo-Yeon; Lee, Dong-Yeon
Abstract : With the reinforced ODP and GWP regulations, clean refrigerants including CO2, energy saving technology for fuel economy, especially focused on development and control strategy for the effective air conditioning system, and heat pump for vehicles have been widely investigated. Recently, the automotive CO2 heat pump for the next generation vehicles as an alternative to that of internal combustion engines has been evaluated and studied as a good option. In this paper, first part is reviewed on the performance characteristics and improvement articles for the conventional automotive air conditioning systems and individual components as well as various alternative refrigerant articles for conventional automotive air conditioning systems. Second part deals with the feasibility of the automotive CO2 heat pump for next generation vehicles without internal combustion engines.